Relationships and diversity of Hordeum vulgare L. (cultivated and wild barley) in Iran measured using cytological parameters - Azadeh Akhavan; Hojjatollah Saeidi (تاکسونومی و بیوسیستماتیک, 2010)
Barley (Hordeum vulgare L.) including cultivated (subsp. vulgare L.) and its wild relative (subsp. spontaneum C. Koch) is considered as the primary gene pool of Hordeum. Wild barley is the progenitor of cultivated barley which is a major crop in the world and economically is the most important species after bread wheat karyotypic studies were performed in 30 wild/cultivated populations of H. vulgare. To look for their relationships and diversity among populations. Based on the results of all the analyzed factors, the most symmetric karyotype was observed in one population belonging to subsp. spontaneum collected from the West and the most asymmetric one observed in a population belonging to subsp. vulgare from the Northwest region. Because the symmetric karyotypes are considered to be more primitive than asymmetric ones, the Western populations of wild barley with the most symmetric karyotype, can be considered as the oldest populations relating to the subsp. vulgare from other regions. Based on the results of this study the coefficient of variability of chromosome length in subsp. spontaneum was higher than that of the subsp. vulgare. Therefore, subsp. spontaneum is primitive and more diverse than subsp. vulgare that can be related to the adaptability of wild barley populations with the highly variable ecological conditions. The results of this study suggest that the karyotype symmetry analysis can be a useful tool to evaluate relationships and diversity of barley populations.